Efficacy and safety of pregabalin and gabapentin in spinal stenosis: a systematic review and meta-analysis - Martínez, Telmo; Mariscal, Gonzalo; de la Rubia Ortí, Jose Enrique; Barrios, Carlos (Frontiers in Pharmacology, 2023)
Background and Objective: Multimodal management of spinal stenosis is on the rise, and central sensitisation inhibitors are playing an essential role in the treatment of central sensitisation processes. Pregabalin and gabapentin are antiepileptic drugs that decrease presynaptic excitability. The aim of this study was to investigate whether the use of pregabalin and gabapentin is effective in the symptomatic management of spinal stenosis, compared to other drugs, by using pain and disability rating scales. We also assessed the safety profile associated with these drugs.We conducted a bibliographic search in the Pubmed, Web of Science, and Cochrane Collaboration Library databases. The inclusion criteria were studies that compared pregabalin or gabapentin to a control group in patients with lumbar spinal stenosis. We included randomized clinical trialsand a comparative retrospective cohort study. The primary clinical endpoints were VAS/NRS and ODI, measured at two, four, eight weeks, and three months, while adverse events and walking distance were also collected. We combined the data using Review Manager 5.4 software.Our meta-analysis included six studies with a total of 392 patients, with a mean age of 60.3 years. We observed no significant differences in VAS scores at two, four, and eight weeks: MD: 0.23, 95%